Nonlinear modeling and simulation of waste energy harvesting system for hybrid engine: fuzzy logic approach - Rahman, Mohammed Ataur; Abdul Razak, Fadhilah; Hawlader, Mohammad Nurul Alam; Rashid, Muhammad Mahbubur (American Institute of Physics, 2013)
Fuel consumption could be cut significantly if waste heat energy of internal combustion engine (ICE) is harvested. Currently, ICEs lose their 42% of energy to exhaust and 28% of energy to the coolant. Several methods for waste thermal energy recovery from ICE have been studied by using supercharger or turbocharger or combined. This study presents the modeling and simulation of coolant based waste energy harvesting system (weHS). The supercharger compressed air gains heat during passing through the inner duct of the weHS while the coolant releases heat. The heated supercharged air is forced to the engine cylinders. The energy harvesting system performance is simulated by varying the supercharged air mass flow rate by keeping constant the coolant mass flow rate and vice versa. The waste energy recovery from the coolant by using weHS is simulated for the coolant flow rate of 2.0 kg/s, 2.5 kg/s, and 3.0 kg/s. The simulations result shows that the waste energies that could be recovered by using weHS are 30.9% for 2.0 kg/s, 32.57% for 2.5 kg/s, and 35% for 3.0 kg/s of the energy that engine lost to the coolant. The efficiency of the engine is expected to increase significantly if weHS is equipped with the engine. The optimum mass flow rate of coolant and mass flow rate of supercharged air are identified by using the fuzzy logic model for the maximum supercharged air temperature of 120 C.